SIMULTANEOUS APPROACH REPAIR FOR COMPLICATED/COMPLEX VESICO-VAGINAL FISTULA - Abdul Rasheed Shaikh; MA Sohail Memon (Journal of University Medical & Dental College, 2013)
ABSTRACT Objective: To evaluate and ascertain the outcome of repair of complicated/complex vesicovaginal fistulae by combined abdominal and vaginal approach. Design: It was an interventional / clinical trial study. Setting and Duration of study: This study was conducted at Almas and Citi Medical Center Larkana between Jan: 2008 to Dec: 2011. Material and Methods: After routine clinical examination and investigations, patients having complicated/complex vesicovaginal fistulae were selected for repair. All patients underwent examination under anesthesia (EUA) and cystoscopy. The patients having associated colonic involvement or with preexisting malignant pelvic pathology were excluded from the study. Postoperative follow up was carried out on weekly basis for 03 to 06 months. Results: Our study comprises of only 12 cases having complicated/complex VVF. The mean age was 35 SD±3.5 years. The mean size of fistula was 3.9 SD±1.2 cm. The ureter and urethra were adjunct with fistula in 03(25%) and 02(%) cases respectively. All cases were treated with aforementioned method and autocystoplasty was carried in 08 (66.5%) cases. The uni-lateral and bilateral ureteric re-implantation was attempted in o1 (8.5%) and o2 (16.5%) cases respectively and double J stent were kept in all these cases. The mean operative time was 145 SD ±23 minutes. Per-operative blood was transfused in all 100% cases. The overall success was achieved in 09/12(75%) cases (Pie; 01). Postoperative recovery was uneventful in all expect 06 (50%) cases who developed adverse can sequences. These were infection (sepsis), self resolving persisting haematuria and wound dehiscence that had occurred in 01(8.5%), 04(33.5%), 01(8.5%) cases respectfully. The mean hospitalization stay was 8.5 SD ±2.5 days. Successful follow up was carried for 06-12 month to all except 02 (17%) cases that bump into failure. The short and long term complications like frequency/dysuria/urgency of micturation, urinary stress incontinence and complains of mild to moderate sort of dyspareunia occurred in 04 (33.5%), 02 (16.5%) and 05(41.5%) cases respectively. Conclusion: We conclude that simultaneous abdominal and vaginal approach permit cystoscopy and access to the vagina and bladder concurrently throughout all stages of the operation. It authorizes the surgeon to excise the fistulous tract judiciously, facilitates to develop better cleavage planes between respective tissues and execute a more satisfactory repair. We recommend a key of success is tension-free auto-cystoplasty in difficult instances.